Adult Burkitt lymphoma- an Island between lymphomas and leukemias. Issue 1 (2nd January 2019) - Turro, James; Singh, Pratiksha; Sarao, Manbeer Singh; Tadepalli, Satish; Cheriyath, Pramil
ABSTRACT: Background : Burkitt lymphoma is a rare, aggressive and rapidly fatal, B-cell non-Hodgkin's lymphoma. It has an incidence of 0.4/100, 000 age-adjusted to the USA standard population. Here we describe the case of a 77-year-old patient who presented with Burkitt lymphoma. Case : A 77-year-old male presented to his primary care physician with fatigue and listlessness and was referred to the hospital with a white blood cell count (WBC)-23.7 K/uL (neutrophils 37%, lymphocyte 11%, blasts 9%) and platelets-19 K/uL. During his stay in the hospital, repeat investigations revealed WBC-29.9 K/uL (neutrophils 22%, lymphocyte 27%, atypical lymphocytes 5%, blasts 20%) and platelets-10 K/uL with no evidence of mucosal bleeds, neck or abdominal masses or generalized lymphadenopathy. Bone marrow aspirate revealed the presence of MYC rearrangements (8q24) on flow cytometry and fluorescent in-situ hybridization (FISH), indicative but not typical of BL. He was transfused with platelets due to a rapidly deteriorating platelet count and episodes of epistaxis. He was discharged after four days with a plan of outpatient chemotherapy over a period of 4 months. An Ommaya reservoir was placed in the right ventricle for intrathecal chemotherapy. After four months of chemotherapy, computerized tomography of the chest, abdomen, and pelvis confirmed remission. A magnetic resonance imaging of the brain a month after completion of chemotherapy revealed metastatic lymphoma in the temporal, parietal and occipital lobes. He was discharged to hospice for palliative care. Conclusion : Unconventional presentations, as seen in our case of a leukemia-like picture in the absence of a bulky disease, are the quagmire that might delay aggressive management and result in poorer outcomes.